Serum Aldosterone Levels in Patients With Diabetic Nephropathy in Relation to Vascular Calcification - Salih, Balqes Hisham; H.Ali, Shatha; I. Allehibi, Khalid (Iraqi Journal of Pharmaceutical Sciences, 2019)
Diabetic Nephropathy(DN) is a complex disease manifested by persistence microalbuminuria occurring due to the interaction between hemodynamic and metabolic pathway that activates the local renin-angiotensin-aldosterone system resulting in a decline in renal functions. This study aimed to quantify the associations between serum aldosterone concentration and fetuin- A as a marker of calcification in type 2 diabetic patients with and without microalbuminuria from one side, and study the possible relationship between aldosterone and fetuin-A with glycemic indices, serum electrolyte, renal function and microalbuminuria and body mass index from the other side. A case-control study involved eighty-six adult subjects classified into three groups after testing urine microalbumin including thirty-two diabetics type 2 patients with positive microalbuminuria and twenty-eight diabetics type 2 patients with negative microalbuminuria and 26 healthy subjects during their visit to AL kindy specialized Center for Endocrinology and Diabetes / Baghdad. Those patients were compared to control group of 26 apparently healthy subjects, fasting blood samples was obtained from each of them in one occasion only to measure: fasting serum glucose, electrolyte, aldosterone, fetuin-A, urea, and creatinine. In addition to glycoheamoglobin, glomerular filtration rate and body mass index. Despite the presence of microalbuminuria in thirty-two of the studied diabetics, there was no positive correlation between aldosterone and fetuin- A, besides that no significant variations in serum aldosterone ,glomerular filtration rate(GFR) values, while both groups showed a significant increase in fasting serum glucose and glycaoheamoglobin ,significant decrease in serum sodium and chloride in comparison with the control group , significant increase was detected in serum fetuin-A mean values in microalbuminuric diabetics. Whereas, negative microalbuminuric diabetics measures expressed a positive correlation between both serum sodium and chloride levels and fetuin -A. The conclusion of this study diabetic patient are prone to vascular calcification (VC) might be due to increase in aldosterone level or due to diabetic itself from this study we can conclude microalbuminuria can occur without a decline in renal function or a change in estimated GFR ,no definite correlation occur between aldosterone and fetuin- A, fetuin- A mean values are higher in diabetic patient with microalbuminuria compared to diabetic patients without microalbuminuria and control group and this referred to uncontrolled diabetes ,aldosterone show a correlation with weight and body mass index while fetuin- A does not show such correlation. In general, electrolyte disturbances (hypernatremia) is more obvious in this study , and its occurrence is due to diabetic (osmotic diuresis) or drugs, while sodium retention which is a sign of aldosterone increment does not occur. Hypochloremia that occur in this study is due to chloride and it is in parallel with sodium level.